Effects of instructional materials in multimedia computer-assisted instruction in teaching folk dance - Lucero, Regel (Edu Sportivo: Indonesian Journal of Physical Education, 2021)
This study aimed to determine the performance level of second year BPED students in teaching folk dance through multimedia computer-assisted instruction and demonstration methods. A quasi-experimental design was utilized. Sixty (60) students participated in the study with two intact heterogeneous classes. A validated researcher-made performance instrument was used to collect data. Descriptive statistics was utilized such as mean, standard deviation, and ANCOVA for the treatment of data. Findings in the pre-test revealed that the performance level of second-year BPED was “developing.” After employing MCAI, the group obtained a “proficient” level of performance in the post-test. The performance level of second-year BPED in the pre-test was “developing.” After employing the demonstration method, the group obtained a “proficient” performance level in the post-test. Students in demonstration method had significantly higher mean scores than those exposed to multimedia computer-assisted instruction. It can thus be concluded that the demonstration method is highly significant in enhancing the performance level of second-year BPED students in teaching folk dance. It was recommended among others that physical educators may conduct more studies related to the good quality of MCAI and may adopt the combination of MCAI and the demonstration methods in teaching folk dance.